STABILITY-INDICATING LC METHOD FOR THE QUANTIFICATION OF MIDAZOLAM ACTIVE PHARMACEUTICAL INGREDIENT AND IN PHARMACEUTICAL FORMULATIONS - Daiane Anzilaggo; Bádila Regina Dalla Costa; Luciana Grazziotin Rossato-Grando; Hellen Karine Stulzer; Charise Dallazem Bertol (Drug Analytical Research, 2018)
A stability-indicating LC method was validated for the quantification of midazolam (MDZ) active pharmaceutical ingredient (API) and in pharmaceutical formulations. Isocratic chromatography was performed on C18 column with mobile phase containing methanol/acetonitrile/water (45:35:20 v/v/v) with 0.4% of triethylamine pH 6.5. The validation included specificity, linearity, accuracy, precision and robustness. In specificity, after acid, basic, neutral, oxidant and thermal degradation, it was found that the concentration of MDZ decreased substantially, with the appearance of peaks representatives of the degradation products, proving the stability-indicating power of the method. The response was linear in the range 50.0 – 250.0 µg.mL-1, with 11.73 µg.mL-1 and 3.87 µg.mL-1 as LOQ and LOD, respectively. Recoveries ranged between 98.68 and 100.41%. The relative standard deviation values for intra and interday precision were 1.11%, 0.82% and 1.47%, respectively. The tablets and injections containing MDZ were approved in the assay and content uniformity. The method can be adopted by pharmacopeias and for routine quality control for analysis of MDZ API, tablets and injection.